Análise do efeito do padrão de entrada no desempenho da comunicação sem fio de medidores residenciais modernos de energia elétrica - Minhoto, Rafael José (Universidade Federal de São Carlos, 2022)
Modern residential smart meters are among the enablers of the smart grid concept. Automatic electric metering is an important part of an energy policy with a focus on implementing new concepts that can provide consumers with user-friendly access to various services, whereby modern residential smart meters can be integrated into the smart grid,for example via a wireless communication interface. In this paper, based on a case study and through experimental analysis with bench and field measurements, the performance of wireless communication employed in a modern residential electricity meter, installed in a metal box entry perpendicular to the roadway, was verified. In the experiments IEEE 802.15.4 compatible devices were used, operating at a frequency of 915MHz, which are used by many manufacturers and utilities in modern residential smart meters.
Analysis of the effect of the power input box on the wireless communication performance of modern residential electricity meters
Keywords: IEEE 802.15.4; ISM 915MHz; Medidor de energia elétrica inteligente; Rádio propagação; Rede sem fio; ZigBee; Radio propagation; Smart meter; Wi-reless network; ENGENHARIAS::ENGENHARIA ELETRICA::SISTEMAS ELETRICOS DE POTENCIA::MEDICAO, CONTROLE, CORRECAO E PROTECAO DE SISTEMAS ELETRICOS DE POTENCIA